Fathers’ Lived Experiences in Parenting Children with Autism Spectrum Disorder - Ega Asnatasia Maharani; Putri Sabrina Uswatun Hasanah; Riana Mashar; Iyan Sofyan (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2026)
The purpose of this study is to explore fathers’ experiences, meanings, and emotional dynamics regarding their role in supporting the development of children with ASD. This study employs a qualitative approach with a phenomenological design to explore fathers’ experiences in the early childhood care of children with ASD. The study was conducted at the Pembina State Special School in Yogyakarta and the Srawung Bocah Inclusive Early Childhood Education Center. Data were collected through in-depth interviews lasting approximately 30–40 minutes with two fathers who have children diagnosed with ASD, and were subsequently analyzed using Braun & Clark’s thematic analysis. The results indicate that fathers’ understanding of their role in caring for children with ASD evolves through a process of acceptance, emotional reflection, and role negotiation between economic responsibilities and caregiving duties. Fathers’ involvement is manifested through adaptive parenting practices, emotional engagement, and collaboration with mothers in supporting their children’s development. Additionally, spirituality, social support, and family dynamics are key factors shaping fathers’ resilience in fulfilling their parenting roles for children with ASD.